Depressive Symptoms Associated with an Earlier Age at Onset Differ as a Function of Race‐Ethnicity: An Exploratory Analysis. (20th December 2022) - Zaman, Andrew; Mena, Pedro Ramon; Adams, Larry D.; Contreras, Maricarmen; Lacroix, Faina C; Tejada, Sergio; Starks, Takiyah D.; Feliciano‐Astacio, Briseida E.; Silva, Concepcion; Caban‐Holt, Allison M; Byrd, Goldie S.; Martinez, Izri; et al.
Abstract: Background: Depression (DEP) is a known risk factor for . However, DEP symptoms vary by race‐ethnicity (e.g. greater somatization among African Americans). The relationship between DEP and AD progression in underrepresented groups is not well‐understood. We hypothesize that certain DEP symptoms will be associated with earlier AAO, and that this relationship is moderated by race‐ethnicity Method: Self‐declared Non‐Hispanic White (NWH), African American (AA), and Hispanic (HI) participants with AD and CDR data were identified from a larger genetic study. Our dataset consisted of 549 persons with a self‐completed GDS (mean CDR = 0.6; 15% NWH, 43% AA, 42% HI), 334 persons with informant completed CSDD (CDR = 1.7; 41% NWH, 20% AA, 39% HI), and 266 persons with self‐reported DEP and anxiety in a medical history exam (CDR = 0.7; 26% NWH, 23% AA, 51% HI). All measures were completed after the onset of AD. Univariate linear regressions examined the relationship between AAO and DEP (total scores and individual items), and race‐ethnicity x DEP interactions after controlling for sex, race‐ethnicity, disease duration, and APOE‐e4 . Result: Self‐reported ( p = 0.04), informant‐reported anxiety (CSDD) ( p = 0.02), and self‐reports of feeling empty (GDS) ( p = 0.02) were associated with an earlier AAO across all groups. Informant‐reports of poor self‐esteem (CSDD) was associated with an earlier AAO overall ( p < 0.01), but an interaction showed that this was not significant in HI ( p = 0.). Unique items associated with an earlier AAO in NHW included higher GDS total scores (p = 0.01), feeling bored (GDS) ( p < 0.01), and perceived problems with memory (GDS) ( p < 0.01). In AA self‐reported DEP was associated with an earlier AAO ( p = 0.02). No items were uniquely associated with AAO in HI. Conclusion: Self‐ and informant‐reported anxiety and self‐reported feelings of emptiness were associated with an earlier AAO in all groups. However, several DEP symptoms associated with earlier AAO differed as a function of race‐ethnicity. We believe our findings suggest that the occurrence of DEP may be culturally or ancestrally influenced, which in turn has a differential impact on AAO in underrepresented groups.